ANALISIS FAKTOR FAKTOR YANG BERPENGARUH TERHADAP IMPLEMENTASI TOOLS DIGITAL MARKETING PADA UMKM DI SURAKARTA - Caldera, Shanda; Hendratmoko, Christiawan (Cattleya Darmaya Fortuna, 2024)
Technological advancements have revolutionized consumer behavior and business operations, particularly through digital marketing. Businesses now heavily rely on digital tools like websites and apps to optimize their online presence and marketing strategies. This shift is essential for Small and Medium Enterprises (SMEs) aiming to bolster their digital capabilities and competitiveness. This study focuses on Surakarta to examine the factors impacting the adoption of digital marketing tools. Employing a quantitative approach, data is gathered from SMEs through questionnaires and secondary sources like literature reviews. The research involves 100 SME respondents selected via Purposive Sampling. Responses are evaluated using a Likert scale (1-5) to gauge mindset, training, and skills related to digital marketing tool implementation. Statistical analyses, including Instrument Testing, Classical Assumption Testing, and Multiple Regression Analysis using IBM SPSS 23, reveal that mindset and skills significantly influence digital tool adoption, whereas training has minimal impact. The study underscores the importance of these factors in SME digitalization efforts, highlighting that while mindset and skills are crucial, there may be additional unexplored variables influencing digital marketing tool adoption. This research contributes insights into enhancing SMEs' digital readiness and strategic use of digital marketing tools in contemporary markets.